MARITAL RAPE: AN ANALYSIS ON RECIDIFFING AND LEGAL-SOCIAL PERSPECTIVES (REMUNOM, 2025)
Marital rape, characterized as sexual violence within the context of marriage, is a crime with deep historical and cultural roots, perpetuated over time due to the patriarchal conception that regarded women as the property of men. In Brazil, the legal evolution surrounding this crime includes the criminalization of marital rape under the Penal Code, the implementation of the Maria da Penha Law, and the recent legislative proposal that explicitly defines marital rape. However, cultural and social resistance still hinders the recognition and effective punishment of this practice. Brazilian legislation, which was previously limited to the concept of rape as solely involving vaginal penetration, was expanded in 2009 to encompass various forms of sexual violence, such as oral and anal sex, with amendments to the Penal Code. The normalization of sexual violence within marriage, fueled by gender stereotypes and cultural norms, has been a significant obstacle in combating marital rape, often treating it as a private matter. Furthermore, it is observed that the reiteration of this practice in the marital sphere not only highlights the persistence of the aggressor but also exposes the structural omission of the victim protection system, which frequently leaves victims helpless in the face of difficulties in breaking continuous cycles of violence. Addressing this challenge requires a profound cultural shift that promotes respect for female autonomy and consent, in addition to a more effective legal system in supporting victims and holding perpetrators accountable. The fight against sexual violence in marriage demands a collective effort, involving legal reforms, public policies, and social awareness to eradicate gender-based violence and ensure equality, rights, and dignity for women.